E-procurement in support of universal health coverage (The World Health Organization, 2015)
Kenya is gearing up for digital bidding on essential medicines' contracts, part of a wave of African countries looking at procurement to improve transparency, bring down costs and support universal health coverage. Gary Humphreys reports.